Lithium ion batteries in electric drive vehicles / edited by Ahmad Pesaran. - Pesaran, Ahmad A. (SAE International, 2016)
This research focuses on the technical issues that are critical to the adoption of high-energy-producing lithium Ion batteries. In addition to high energy density / high power density, this publication considers performance requirements that are necessary to assure lithium ion technology as the battery format of choice for electrified vehicles. Presentation of prime topics includes: *Long calendar life (greater than 10 years) *Sufficient cycle life *Reliable operation under hot and cold temperatures *Safe performance under extreme conditions *End-of-life recycling To achieve aggressive fuel ec.
Keywords: Electric vehicles -- Batteries.; Lithium ion batteries.